The doctrine of ultra vires a comparative study of the (law) position in Malaysia and the United Kingdom / Hamidah Mohd. Akib - Mohd. Akib, Hamidah (Faculty of Law, 1982)
One consequence of the artificial nature of a company as a legal person is that inevitably it can act only through the agency of a natural persons. Another consequence is that a company incorporated by or under a statute can pursue only those objects which are expressly or implicitly conferred upon it, implied powers being restricted to those which are reasonably incidental to the accomplishment of its authorised objects. The impact of these upon the outside world involves a consideration of the ultra-vires doctrine. As a result of complexity and confusion, arises from the multiplicity of the interests involved in the operation of a corporation, it may be useful 2 to set these out . Firstly the company itself is a separate legal entity.^ The essential feature of separationess is despite appearance even the "one-man company" is different in law from that one man e.g. the Board of Directors is not the company and even the one and only surviving shareholder of a company is not the company. The company is a separate entity. Secondly, the Directors of a company appear to be agents, trustees, employees or even owners but these are only different ways of looking at that complex of rights, duties and responsibilities and liabilities which we label Directors: Directors are not company. Thirdly, the shareholders in one sense own the company, and in a partnership they would all have the right to manage the business, yet their rights are restricted to voting at meetings, receipt of dividends if declared and the receipt of information about the state of the company and their liability is usually restricted to the paying up of the amount unpaid (if any) on their shares. Finally an interest of a different nature is that of the class of creditors whose interest are in conflict with the others especially when a company is in financial trouble. Thus when discussing the capacities of companies and the ultra-vires doctrine, we will find that the case law reflects these diverse interests.